(untitled) (Contemporary Mathematics, 2024)
Iron oxide, Silver, Aluminium oxide, these nanoparticles individually or combined help in drug delivery especially aluminium oxide nanofluid used in an anti-blood pressure drug called ’Telmisartan’. Alumina and silver particles are used in manufacturing nanocomposites which have more antimicrobial properties. This is the reason for the current study of ternary nanofluids natural convective flow and efficacy of energy transfer in a bi-directionally sheet. Currently, ternary nanofluids (Fe3O4, Ag, Al2O3) are being taken for analysis. Usual water (H2O) is the conventional base fluid. Two different combinations of ternary nanofluids are used to get the average heat transfer rate, mixture ratios (Fe3O4 + Ag) and (Fe3O4 + Ag + Al2O3) when subjected to a variety of physical influences, including thermal radiation, magnetic fields, heat production and absorption, and nanoparticle volume amount. It is possible to solve the developed set of equations numerical results using the Keller box (finite differences) method with the help of MATLAB programming. This method helps in solving higher order partial differential equation (PDEs) to ordinary differential equation (ODEs). The investigations findings demonstrated that the ternary hybrid nanofluids specific heat capacity is directly impacted by temperature. Numerical solutions for Nusselt number, velocity profile, skin friction coefficient, temperature profiles have represented with the help of graphs and tables. The ternary hybrid nanoflow (Fe3O4 + Ag + Al2O3/H2O) transmits more energy for increasing volume fractions, comparing to the hybrid nanofluid (Fe3O4 + Ag/H2O). The study reveals the fact that metal oxides transfer more heat from the system than that of metals. The estimated error of heat transfer rate is higher in alumina nanoflow followed by silver and iron oxide nanofluid flows. The streamlines are equally spaced, but the energy flow amount is higher for the case M, S = 1 than M, S = 2. But in the case of stretching ratio parameter, the amount energy flow in α = 0.5 > α = 1.0. An equal amount of energy flow is observed for varied Biot number.